10-Year single center experience in lower limb reconstruction with free muscle flaps – factors influencing complications in 266 consecutive cases. Issue 1 (28th February 2023) - Besmens, Inga S.; Frueh, Florian S.; Gehrke, Christina; Knipper, Sophie; Giovanoli, Pietro; Calcagni, Maurizio
Abstract: The anatomy and technique of free muscle flaps – in particular gracilis flap and latissimus dorsi flap – in lower extremity reconstruction have been well described. There is a paucity of data on potential risk factors in larger patient series that affect the outcome. The objective of this study was to address this lack of knowledge by reporting outcomes and complications of free muscle flaps as a primary option in lower extremity reconstruction. From 2009 to 2020, a total of 253 consecutive patients with soft tissue defects of the lower limb from trauma, infection or malignancies underwent lower extremity reconstructive surgery with 266 free muscle flaps. Complications requiring revision surgery were noted in 36.1% of cases. Total flap loss occurred in 10.5% of cases. Patients requiring revision surgery were older, more likely to be female, more likely to be active smokers, and more likely to have a higher ASA score. Lower extremity reconstruction with free muscle flaps has a relevant complication rate that both patient and reconstructive surgeon need to be aware of. Prospective studies should try to further assess the factors affecting the outcome.